2021
DOI: 10.1109/tetc.2020.2982461
|View full text |Cite
|
Sign up to set email alerts
|

Access Control for Implantable Medical Devices

Abstract: The telemetry incorporate in the new generation of Implantable Medical Devices (IMDs) allows remote access and reprogramming without interfering with the daily routine of their holders. Despite the benefits of this new feature, such remote access raises new threats related to the access of unauthorized entities to IMDs. Cardiac implants represent the most deployed types of IMD nowadays. Current solutions, to control their remote access, usually use a single feature for authentication. However, this feature is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Exploitation of wireless networks [105]- [106], Jamming [107], Reconnaissance [108]- [109], industrial data thefts and espionage [110]- [111], Disclosure of Information [112]- [113], interception [105], unauthorized access [114], GPS network exploitation [105] [115]- [116].…”
Section: Cps Threatsmentioning
confidence: 99%
“…Exploitation of wireless networks [105]- [106], Jamming [107], Reconnaissance [108]- [109], industrial data thefts and espionage [110]- [111], Disclosure of Information [112]- [113], interception [105], unauthorized access [114], GPS network exploitation [105] [115]- [116].…”
Section: Cps Threatsmentioning
confidence: 99%
“…Therefore, after demodulation, a carrier creates sensitivity at the receiver's normal frequency, modulated with a standard test signal that provides a data signal with a defined BER of 10 − 2 specified effective message ratio of 80%. A new generation of M Ss indicates that these devices will play new roles in a variety of healthcare settings [28], [29] Passive components such as reception antennas, adaptation, and reception filters are examples of improving the device's sensitivity during the reception. On the other hand, there are several analytical methods to improve range.…”
Section: Related Work and Contributionsmentioning
confidence: 99%
“…Weak programming practices can generate significant technical debt [188,189] in wearable sensing systems. Examples in the literature of possible attacks include remotely accessing implantable cardiac devices to make them fail [190] or to violate users' privacy [191]. After Corbin [192] reported that former U.S. Vice President Dick Cheney's pacemaker had software vulnerabilities that could enable hackers to cause heart attacks remotely, the former Vice President disabled the remote access capabilities of his pacemaker.…”
Section: Vulnerability Description Examples Of Attacksmentioning
confidence: 99%